Competitiveness Analysis of Smallholder Oil Palm Farming in Rimbo Ilir District, Tebo Regency - Lilis Sartika Pardede; Saidin Nainggolan; Ardhiyan Saputra (Politeknik Pertanian Negeri Samarinda, 2025)
This study examines the competitiveness of smallholder oil palm plantations in Rimbo Ilir District, Tebo Regency, and evaluates how government policies affect their performance. Using the Policy Analysis Matrix (PAM), this study analyzes comparative and competitive advantages, the impact of policies on inputs and outputs, and the sensitivity of these policies. Conducted in Sari Mulya, Sumber Agung, and Karang Dadi Villages during April–May 2025, this study found that smallholder oil palm plantations in the region have strong competitiveness, reflected in PCR (0.28) and DRCR (0.5458) values ​​below 1. Policy indicators indicate that government interventions do not fully protect tradable inputs (NPCI > 1) and act as a disincentive to output (NPCO < 1), while overall input–output policies remain ineffective (EPC < 1). Sensitivity tests indicate that despite an increase in input prices (12%–25%) or a 10% decrease in output prices, oil palm plantations maintain their competitive and comparative advantages. In conclusion, smallholder oil palm plantations in Rimbo Ilir Regency remain highly competitive and worthy of further development.